2001
DOI: 10.1146/annurev.ecolsys.32.081501.114002
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Regional Deep-Sea Species Diversity

Abstract: ▪ Abstract  Most of our knowledge of biodiversity and its causes in the deep-sea benthos derives from regional-scale sampling studies of the macrofauna. Improved sampling methods and the expansion of investigations into a wide variety of habitats have revolutionized our understanding of the deep sea. Local species diversity shows clear geographic variation on spatial scales of 100–1000 km. Recent sampling programs have revealed unexpected complexity in community structure at the landscape level that is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
628
4
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 639 publications
(679 citation statements)
references
References 162 publications
41
628
4
6
Order By: Relevance
“…A positive link with productivity has often been considered as the major cause of deep-sea diversity patterns, although the direct evidence for this is currently scarce and ambiguous (Levin et al 2001). Tietjen (1989) Along with the depth-related effect of productivity, our regressions for α diversity also include depth per se as an independent term (Table 2, Models 1, 2, and 6), indicating the existence of some other depthrelated factor(s) that increases richness.…”
Section: Diversity Measures: Methodsological Aspectsmentioning
confidence: 87%
See 1 more Smart Citation
“…A positive link with productivity has often been considered as the major cause of deep-sea diversity patterns, although the direct evidence for this is currently scarce and ambiguous (Levin et al 2001). Tietjen (1989) Along with the depth-related effect of productivity, our regressions for α diversity also include depth per se as an independent term (Table 2, Models 1, 2, and 6), indicating the existence of some other depthrelated factor(s) that increases richness.…”
Section: Diversity Measures: Methodsological Aspectsmentioning
confidence: 87%
“…For example, in a large-scale study, Rombouts et al (2009) found a significant inverse relationship of marine epipelagic (0−200 m) copepod diversity with chl a content, indicating that diversity is high in oligotrophic regions. There are a number of hypotheses to explain the 'decrease phase' of the diversity−productivity relationship, and some of these hypotheses are applicable to marine meiofauna (see Rosenzweig 1995, Levin et al 2001 for a review).There is some additional, though indirect, evidence for negative effects of productivity in the intertidal and subtidal zones. A positive relationship between total meiofaunal abundance and the input of organic matter has been reported repeatedly (De Troch et al 2006, Mokievsky et al 2007, Lampadariou et al 2009).…”
mentioning
confidence: 99%
“…8. Combination of the TROX model (trophic condition and oxygen concentration of Jorissen et al, 1995;Jorissen, 1999) and the parabolic curve of Levin et al (2001) explaining the relationship of local species diversity and productivity (modified after Gooday, 2003). Diversity is low in highly oligotrophic areas such as the Arctic Ocean where food supply (flux of organic carbon to the seafloor = productivity) is very low and thus incapable of sustaining large number of species.…”
Section: Resultsmentioning
confidence: 99%
“…A present day analogue for describing the relationship of diversity and paleoproductivity noted in the Caribbean can be explained by combining the TROX model (trophic condition and oxygen concentration of Jorissen et al, 1995;Jorissen, 1999) and the parabolic curve of Levin et al (2001), which explains the relationship of local species diversity and productivity (Gooday, 2003;Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation